MENGIDENTIFIKASI KECERDASAN ANAK - Sulaiman, Umar (STAIN Sorong, 2015)
The development of Indonesian society’s life attitude in the postreformation era has made a lot of changes, including language as the use of foreign language at schools having international and international pioneering standard. Character construct covers the basic strategy in overcoming those phenomenons through educational system, especially the bahasa Indonesia education starting from the curriculum, methods, learning books, skills, personality, and reference. In addition, preparing dedicated profesional teachers should be necessity. There are many intelegent must be improved ticher to student minimally, smart word, smart picture, smart logic, smart body, smart music, smart people, smart nature, and self-smart. This article discribes about that.